A quantitative perspective on optimal monetary policy cooperation between the US and the euro area - Stéphane Adjemian; Matthieu Darracq Pariès; Frank Smets (European Central Bank (ECB), 2008)
The objective of this paper is to examine the main features of optimal monetary policy cooperation within a micro-founded macroeconometric framework. First, using Bayesian techniques, we estimate a two-country dynamic stochastic general equilibrium (DSGE) model for the United States (US) and the euro area (EA). The main features of the new open economy macroeconomics (NOEM) are embodied in our framework: in particular, imperfect exchange rate pass-through and incomplete financial markets internationally. Each country model incorporates the wide range of nominal and real frictions found in the closed-economy literature: staggered price and wage settings, variable capital utilization and fixed costs in production. Then, using the estimated parameters and disturbances, we study the properties of the optimal monetary policy cooperation through welfare analysis, impulse responses and variance decompositions.
Keywords: E4; E5; F4; 330; Bayesian estimation; DSGE Models; new open economy macroeconomics; optimal monetary policy; Geldpolitik; Internationale Zusammenarbeit; Neue Makroökonomik offener Volkswirtschaften; Bayes-Statistik; Dynamisches Gleichgewicht; Theorie; EU-Staaten; USA